Characterization of a Vacuolar Pyrophosphatase in Trypanosoma brucei and Its Localization to Acidocalcisomes - Rodrigues, Claudia O. (American Society for Microbiology, 1999)
Inorganic pyrophosphate promoted the acidification of an intracellular compartment in permeabilized procyclic trypomastigotes of Trypanosoma brucei, as measured by acridine orange uptake. The proton gradient generated by pyrophosphate was collapsed by addition of nigericin or NH(4)Cl. Pyrophosphate-driven proton translocation was stimulated by potassium ions and inhibited by KF, by the pyrophosphate analogs imidodiphosphate and aminomethylenediphosphonate (AMDP), and by the thiol reagent p-hydroxymercuribenzoate at concentrations similar to those that inhibit the plant vacuolar H(+)-pyrophosphatase (PPase). The proton translocation activity had a pH optimum around 7.5 and was partially inhibited by 7-chloro-4-nitrobenz-2-oxa-1,3-diazole (10 μM) and unaffected by bafilomycin A(1) (40 nM), concanamycin A (5 nM), sodium o-vanadate (500 μM), oligomycin (1 μM), N-ethylmaleimide (100 μM), and KNO(3). AMDP-sensitive pyrophosphate hydrolysis was detected in both procyclic and bloodstream trypomastigotes. Measurements of acridine orange uptake in permeabilized procyclic trypomastigotes in the presence of different substrates and inhibitors suggested the presence of H(+)-ATPase, H(+)-PPase, and (ADP-dependent) H(+)/Na(+) antiport activity in the same compartment. Separation of bloodstream and procyclic trypomastigote extracts on Percoll gradients yielded fractions that contained H(+)-PPase (both stages) and H(+)/Na(+) exchanger (procyclics) activities but lacked markers for mitochondria, glycosomes, and lysosomes. The organelles in these fractions were identified by electron microscopy and X-ray microanalysis as acidocalcisomes (electron-dense vacuoles). These results provide further evidence for the unique nature of acidocalcisomes in comparison with other, previously described, organelles.